Effects of polyetherimide sizing involving carbon nanotubes on interfacial performance of carbon fiber/polyetheretherketone composites. (16th May 2021) - Liu, Hansong; Zhao, Yan; Chen, Fan; Li, Na; Sun, Mingchen; Zhang, Tianyi; Sun, Tianpei; Wang, Kai; Du, Shanyi
Abstract: The interaction between carbon fiber (CF) and thermoplastic resin presents weakened characteristic, which can be problematic of composites in structural applications. Therefore, it is of great significance to research techniques of CF surface modification to strengthen the interface of composites. Herein, based on the optimization of emulsion composition, polyetherimide (PEI) sizing involving carbon nanotubes (CNTs) was applied on CF surface to enhance the interface of CF/polyetheretherketone (PEEK) composites. The surface morphology, chemical characteristic, and surface energy of modified CF illustrate the effectiveness of this method, and the micro as well as macro interfacial properties of as‐prepared modified CF/PEEK demonstrate the increased tendency. This work may shed some light on industrialized application of the sizing agent for CF reinforced high‐performance engineering plastic composites.